Projetos pedagógicos de linguagem: estratégia de ensino para aprendizagem ativa de leitura e escrita - Lima, Estela Lia Teixeira Moreira (2022)
This study aims to investigate the effectiveness of a pedagogical language project as a teaching and learning strategy that can mobilize fundamental skills and competences to compose the formative path of students and teachers. This is because, even though it is not an innovative perspective, the work with projects promotes a vision about knowledge and the curriculum that can lead to fundamental changes in schools (HERNANDÉZ, 1998). For students, this change comes from the perspective of making them recognize themselves as active in the learning process in which they participate, making them assume the position of active learners (BELL and KAHRHOFF, 2006). For teachers, the projects enable the full exercise of tasks that are required in a significant pedagogical practice – the exercise of dealing with cognitive phenomena, such as anticipation, forecasting and planning –, resulting in the formation of action plans from goals and training intentions, in a dynamic of constant changes in the path that prepares them to deal with the unforeseen and learn from it (PASSARELLI, 2002). From this, the general objective of this work is outlined: to investigate the teaching of social practices of reading and writing through pedagogical language projects in order to provide active learning. The specific objectives, in turn, are: (1) to identify, from a theoretical and empirical perspective, the teacher's role in planning, mediating, and evaluating pedagogical proposals for projectbased reading and writing and (2) to present a project proposal pedagogical language developed with students from the 5th year of Elementary School I. The theoretical framework that supports the development of this research linked to the concepts of language, multiliteracies, pedagogical projects and active learning is based on the ideas of Bender (2014), Dolz and Schneuwly (2004), Hernández (1998), NLG (1996) and Vickery (2016). Along with the theoretical exposition, this work analyzes the conception, planning, development, and results of a pedagogical project implemented in a private school in the east side of São Paulo (SP). The analysis of planning, mediation and evaluation strategies and the report of the experience lived with the implementation of each project task consolidated the corpus of analysis of this work, based on the perspective of hermeneutic phenomenology (VAN MANEN, 1990), which includes a descriptive and interpretive approach. The results show that pedagogical projects offer a learning trajectory that can lead students to take the place of active learners